2020
DOI: 10.1021/acsnano.0c06360
|View full text |Cite|
|
Sign up to set email alerts
|

Encapsulating Ultrafine Sb Nanoparticles in Na+ Pre-Intercalated 3D Porous Ti3C2Tx MXene Nanostructures for Enhanced Potassium Storage Performance

Abstract: Taking into consideration the advantages of the highly theoretical capacity of antimony (Sb) and abundant surface redox reaction sites of Na+ pre-intercalated 3D porous Ti3C2T x (Na–Ti3C2T x ) architectures, we elaborately designed the Sb/Na–Ti3C2T x hybrid with Sb nanoparticles homogeneously distributed in 3D porous Na–Ti3C2T x architectures through a facile electrostatic attraction and carbothermic reduction process. Na–Ti3C2T x architectures with more open structures and larger active specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 77 publications
2
65
0
Order By: Relevance
“…As shown in Figure 1 g and Figure S5, the presence of the unique signal of K in 3D K + ‐Ti 3 C 2 T x confirms the success of our K + pre‐intercalation strategy. There are two satellite peaks for Ti 2p 1/2 and Ti 2p 3/2 at 459.8 and 454.8 eV, which can be further deconvoluted to the characteristic peaks corresponding to Ti−C bonds, Ti(II) and Ti−O bonds, respectively (Figure S5a,d,g) [21, 29] . More importantly, three major peaks derived from O 1s (Ti‐O, C‐Ti‐O x and C‐Ti‐OH x ) and the strong F 1s spectra reflect the existence of O, OH, and F functional groups on the Ti 3 C 2 T x surface (Figure S5b,e,h) [35] .…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure 1 g and Figure S5, the presence of the unique signal of K in 3D K + ‐Ti 3 C 2 T x confirms the success of our K + pre‐intercalation strategy. There are two satellite peaks for Ti 2p 1/2 and Ti 2p 3/2 at 459.8 and 454.8 eV, which can be further deconvoluted to the characteristic peaks corresponding to Ti−C bonds, Ti(II) and Ti−O bonds, respectively (Figure S5a,d,g) [21, 29] . More importantly, three major peaks derived from O 1s (Ti‐O, C‐Ti‐O x and C‐Ti‐OH x ) and the strong F 1s spectra reflect the existence of O, OH, and F functional groups on the Ti 3 C 2 T x surface (Figure S5b,e,h) [35] .…”
Section: Resultsmentioning
confidence: 94%
“…They also encapsulated ultrafine Sb nanoparticles in porous Ti 3 C 2 T x through electrostatic attraction resulting in enhanced electrochemistry performance. [99]…”
Section: Sodium/potassium-ion Batteriesmentioning
confidence: 99%
“…The D K values for the potassiation process varied in range of 10 –10 to 10 –11 cm 2 s −1 and were 10 –8 ~ 10 –10 cm 2 s −1 for the depotassation process. The high K + diffusion coefficients confirmed that the ternary Cu 1.75 Se-MXene-CNRib anode allows rapid K + migration and storage at a more efficient kinetic behavior, and it can be a competitive anode for PIBs [ 21 , 36 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is very clear that the novel ternary MSe-MXene-CNRib heterostructures are capable of exceptional Na and K ions storages with excellent capacity at both low and high rates [14,22,28,[33][34][35][36][37][38][39]. The exceptional electrochemical performance is mainly attributed to the unique combination of 2D nanomaterials, which provide abundant active storage sites on the surfaces and at the interfaces for the large Na and K ions and allow ultrafast ion transport and migration within the porous structures.…”
Section: Theoretical Calculations Of Mse-mxene-cnrib Heterostructurementioning
confidence: 99%